2015
DOI: 10.1002/hed.24034
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive function of low‐dose deguelin on the invasion of oral cancer cells by downregulating tumor necrosis factor alpha–induced nuclear factor‐kappa B signaling

Abstract: The low-dose deguelin suppressed the invasion and migration of oral cancer by downregulating TNF-α-induced NF-κB signaling. © 2015 Wiley Periodicals, Inc. Head Neck 38: E524-E534, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 42 publications
(82 reference statements)
0
21
0
Order By: Relevance
“…Here, we demonstrated that deguelin has a combination effect with AG1478 in PIK3CA mutant HNSCC cells. Previously, deguelin alone was reported to induce apoptosis via AKT signaling inhibition, autophagy, and CDK4/Survivin degradation at high doses (50 or 100 μM) [20] and to suppress invasive ability at a low dose (0.1 μM) in HNSCC cells [23]. Although deguelin was reported to sensitize HNSCC cells to 5-fluorouracil (FU) [20], to the best of our knowledge, this is the first report that deguelin has a combination effect with an EGFR TKI for induction of apoptosis in HNSCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we demonstrated that deguelin has a combination effect with AG1478 in PIK3CA mutant HNSCC cells. Previously, deguelin alone was reported to induce apoptosis via AKT signaling inhibition, autophagy, and CDK4/Survivin degradation at high doses (50 or 100 μM) [20] and to suppress invasive ability at a low dose (0.1 μM) in HNSCC cells [23]. Although deguelin was reported to sensitize HNSCC cells to 5-fluorouracil (FU) [20], to the best of our knowledge, this is the first report that deguelin has a combination effect with an EGFR TKI for induction of apoptosis in HNSCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Xiao et al (2016) found that miR-503 inhibited hepatocellular carcinoma cell growth, which is consistent with our results in which the Hep-mock cells had low cell viability with high miR-503 expression under the condition in which TNF-α was introduced for cell cultivation. Previous studies have demonstrated that TNF-α can activate NF-κB (Liu et al, 2015; Zhao et al, 2015), and NF-κB can promote miR-503 transcription (Caporali et al, 2015). Our results support those findings; we found that the expression of miR-503 and n65 were upregulated in the TNF-α-induced Hep-mock cells.…”
Section: Discussionmentioning
confidence: 99%
“…These inhibitory effects were mediated by the suppression of TNFα–induced activation of IκB kinase, which led to the inhibition of IκB phosphorylation, NF‐κB transcriptional activity, and matrix metalloproteinase 2 (MMP2) expression. This finding is crucial to increasing patient survival rates because cancer morbidity and mortality are chiefly attributed to cancer metastasis …”
Section: Anticancer Effects Of Deguelinmentioning
confidence: 99%
“…This finding is crucial to increasing patient survival rates because cancer morbidity and mortality are chiefly attributed to cancer metastasis. 54 Furthermore, Mehta et al 55 showed that deguelin treatment resulted in inhibition of the proliferation of 4T1 mammary cancer cells, which are highly aggressive estrogen receptor/progesterone receptor-and human epidermal growth factor receptor 2-negative cells that mimic stage IV breast cancer progression. In mouse models, deguelin also reduced the incidence of lung metastasis after intravenous 4T1 cell administration.…”
Section: Preventing Metastasismentioning
confidence: 99%